(untitled) (Research, Society and Development, 2021)
This study aimed to determine the effects of physical, chemical and water-holding capacity of Quartzarenic Neosol, Red Latosol and Red Nitosol on tree growth, physicomechanical properties and anatomical features of wood from 33-year-old C. citriodora plantations. More clayey soils with higher water availability, such as Red Latosol and Red Nitosol, increased the mean annual increment and heartwood percentage. In more sandy soils, such as Quartzarenic Neosol, density increased, but the size and diameter of fibers and vessels decreased, and both fiber cell wall thickness and frequency of vessels and rays increased. Wood shrinkage and mechanical properties did not differ between soils. We observed a gradual increase in the anatomical, physical and mechanical characteristics in the pith-bark direction. The uniformity index showed that Quartzarenic Neosol and Red Latosol soils produced more homogeneous woods. We concluded that soil texture and water availability influenced tree growth, anatomical properties and wood density.